The role of Islamic spirituality in overcoming depression: A literature review - Amir, Arman Muhammad (Privietlab, 2026)
This study aimed to examine the role of Islamic spirituality in addressing depression, particularly among young people, through the practices of dhikr (remembrance of God), prayer, supplication, trust (tawakal), patience, and consent (privacy), which effectively reduce depressive symptoms. This research methodology uses a literature review with a descriptive analysis approach to analyze Islamic spiritual practices and their effectiveness in addressing depression among adolescents. Data were obtained from scientific journals, books, and academic publications that discussed the relationship between Islamic spirituality and mental health. The results of this literature review indicate that the higher a person's level of Islamic spirituality, the better their psychological well-being, including resilience to depression. Islamic psychology makes a vertical relationship with Allah SWT the primary foundation for protecting mental health, in line with Surah Ar-Ra'd/13:28, which states that only by remembering Allah can the heart be at peace. Therefore, the practice of dhikr provides peace of mind and soul, and prevents symptoms of depression.